Effect of ions released and pH of two glass ionomer cements in human gingival fibroblasts = Efecto de la liberación de iones y pH de dos cementos de ionómero de vidrio en fibroblastos gingivales humanos - Vega Jiménez, Alejandro Luis
Conventional glass ionomer cements are used as dental provisional restorative materials, which present several advantages such as adhesion to the tooth mineral phase among others. On the other hand, the knowledge about biological property of glass ionomers shows various approaches and results. In this work, it was studied the in vitro biological response of human gingival fibroblasts in contact with commercial cements of glass ionomer: Mirafil® and Ionglass® and with their extracts, according to ISO 10993. The extracts of the cements, in which the cells were cultured, were adjusted at different concentrations ranging 0.1% to 100%. The cellular metabolic activity of gingival fibroblasts was measured using the Alamar Blue® reagent. The results showed a significant effect on the cellular metabolic activity correlated with the concentration of liberated ions (Al³+ and Ca²+) for both ionomers, as well as the pH variations of the culture media. This could mean that the cellular metabolic activity is substantially influenced by ions and pH of the cell culture.